PENGARUH INFLASI AKSES MODAL DAN PELATIHAN KEWIRAUSAHAAN TERHADAP KINERJA UMKM DITENGAH TANTANGAN EKONOMI - Arti, Pidia; Hapid; Hamid, Rahmad Solling (ITB AAS Indonesia Surakarta, 2025)
MSMEs with inflation, access to capital and good entrepreneurship training tend to be able to improve MSME performance effectively. This study aims to examine the effect of inflation, access to capital, and business training on MSME employee productivity in the context of the economic crisis in Palopo City. The population of this study consisted of all MSME actors in Palopo City totaling 50 people, and all members of the population were sampled. This study uses a quantitative approach with primary data collected through online questionnaire distribution. Data analysis techniques include instrument testing, multiple linear regression testing, and hypothesis testing analyzed using the SPSS 25 application. The results of the t-test show that inflation, access to capital, and entrepreneurship training have a positive and significant effect on MSME performance. Meanwhile, the f-test shows that simultaneously, inflation, access to capital and entrepreneurship training have a positive and significant effect on MSME performance.